2014
DOI: 10.1016/j.jtcvs.2013.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Balancing curability and unnecessary surgery in the context of computed tomography screening for lung cancer

Abstract: The frequency and extent of surgery for nonmalignant disease can be minimized in a CT screening program and provide a high cure rate for those diagnosed with lung cancer and undergoing surgical resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 27 publications
1
43
0
Order By: Relevance
“…Nonrandomized trials have shown equivalence between lobectomy and limited resection for cancers manifesting as part-solid and solid nodules smaller than 30 mm (24)(25)(26), and there are ongoing randomized surgical trials comparing lobectomy with limited sublobar resection for cancers manifesting in such nodules. The role of nonsurgical therapy for these lesions, such as radiation (27) or image-guided ablative therapy, are not yet well explored.…”
Section: Discussionmentioning
confidence: 99%
“…Nonrandomized trials have shown equivalence between lobectomy and limited resection for cancers manifesting as part-solid and solid nodules smaller than 30 mm (24)(25)(26), and there are ongoing randomized surgical trials comparing lobectomy with limited sublobar resection for cancers manifesting in such nodules. The role of nonsurgical therapy for these lesions, such as radiation (27) or image-guided ablative therapy, are not yet well explored.…”
Section: Discussionmentioning
confidence: 99%
“…Wilson and colleagues [11] report that 34.1% of patients who underwent thoracotomy or video-assisted thoracoscopic surgery (VATS) for suspected lung cancer were diagnosed with benign disease [11]. However, Crestanello and associates [12] from the Mayo Clinic and Flores and associates [13] from the International Early Lung Cancer Action Program (I-ELCAP) have reported considerably lower rates of 18.2% and 11.0%, respectively.…”
mentioning
confidence: 99%
“…JCOG0202 demonstrated that irinotecan/cisplatin showed no advantages over cisplatin/etoposide for patients with limited-stage SCLC (100), whereas JCOG 0509 found the promising topoisomerase II inhibitor amrubicin inferior in combination with cisplatin as compared with etoposide/cisplatin (101). Also, a key American Society of Clinical Oncology presentation of a Japanese phase 3 study now casts doubt on the utility of prophylactic cranial irradiation in patients with extensive-stage SCLC, as in this study the prophylactic cranial irradiation arm had inferior survival outcomes despite a reduction in CNS metastases (102), whereas a European phase III study demonstrated clinical benefit for consolidation thoracic radiotherapy in the treatment of extensive-stage SCLC (103).…”
Section: Small Cell Lung Cancermentioning
confidence: 86%